Outbreak of Nontuberculous Mycobacteriosis with Dematiaceous Fungus Co-infection in Aquarium-reared Sharphead Flyingfish (Hirundichthys oxycephalus) - Inohana, Mari; Fukano, Hanako; Srivorakul, Saralee; Wada, Shinpei; Kurata, Osamu; Tanaka, Yoshiaki; Tomaru, Kentaro; Komine, Takeshi (Fish Pathology, 2021)
An episode of serial mortality occurred in a population of wild-caught, aquarium-reared sharphead flyingfish Hirundichthys oxycephalus. ​Most diseased fish had ulcerative hemorrhagic lesions on the skin, especially on the head, and displayed multiple, fine, whitish nodules scattered on the internal organs, including the kidney, spleen and liver. ​Histopathological examination revealed the nodules to be granulomatous lesions consisting of epithelioid cells with a thin outermost rim of fibroblasts and connective tissue, and the central caseous core of the granulomas was associated with acid-fast bacilli. ​Though the granulomatous lesions were systemically present in the major internal organs, the most severe lesions were in the kidney and spleen. ​In addition, melanized fungal hyphae were also found in the kidney and spleen. ​Acid-fast bacterial strains were isolated from affected fish and most were identified as Mycobacterium marinum by molecular examination. ​A few dematiaceous fungal strains were also isolated from some fish and identified as Exophiala aquamarina by morphological and molecular examination. ​This is a novel description of a case of co-infection of a nontuberculous mycobacterium (M. marinum) and a dematiaceous fungus (E. aquamarina) in a flyingfish species.